An event-based analysis of Huawei's strategic path and style - Jian Zhang; Pierre Vialle (International Telecommunications Society (ITS), 2014)
Founded in 1987 as a sales agent of PBX (private branch exchange), Huawei has become one of the world's leaders in the ICT Industry. It initially had little technological and management knowledge, but competed with the incumbents including Sino-foreign joint ventures (JVs), state-owned firms, and foreign vendors. In 2013, Huawei has become the world's largest telecom network infrastructure vendor. It operates business in more than 140 countries, and foreign markets represent two thirds of its revenue. It is one of a few vendors able to provide end-to-end telecommunications equipment and solutions. 44% of the 140,000 employees are R&D engineers, and 10% to 20% of its annual revenue is invested in R&D. In a recently published analysis of patents 'Patent Power 2012' by IEEE Spectrum, Huawei is the only Asian firm in the top 20 in communication/internet equipment category. As other Chinese firms, Huawei has benefitted from specific country factors, and in particular from the impact of policies. The Chinese public policy has skilfully used inter-organisational relationships and networks in order to develop a Chinese 'knowledge pool' with worldwide connections (Vialle 2007, 2009). the development of the University system, the close links between research centres and industry, the development of JVs, and focused research projects, have created a system which is not only able to acquire, produce and diffuse publicly available and rather codified knowledge, but also to convert tacit knowledge endogenously generated by industrial activity into a more codified form. One benefit for Chinese Telecom companies has been the large availability of relatively cheap qualified manpower.
Keywords: 330; Huawei; China; Telecommunications; catching-up; latecomer